Satisfaction of short-term rental customers: empirical study in Portugal - Machado, Maria João; Patuleia, Mafalda; Dias, Álvaro; Estêvão, João (Business: Theory and Practice, 2021)
This study has three specific objectives: to analyse the association between the characteristics of the accommodation and the satisfaction of short-term rental customers; to analyse whether customer satisfaction is associated with them recommending the accommodation; and to analyse which satisfaction dimensions most influence the overall satisfaction of short-term rental customers. Data collection was carried out through an online survey aimed at individuals residing in Portugal, who stayed overnight in a short-term rental accommodation within the national territory. One thousand valid inquiries were collected. The results suggest the following as main contributions: the demonstration that the type of accommodation and the neighbourhood are associated with the satisfaction of short-term rental customers; the validation of the importance of customer satisfaction in terms of them recommending the accommodation; the identification of the importance of the various satisfaction dimensions as determinants of the overall satisfaction of the short-term rental customer.